Use of latex agglutination technique for detecting Legionella pneumophila (serogroup 1) antibodies. - Holliday, M G (1990)
Following the outbreak of Legionnaires' disease in Stafford in 1985, 500 serum samples were submitted to the indirect immunofluorescence antibody test and a latex agglutination. Latex agglutination using ultrasonically disrupted Legionella pneumophila antigens coupled to latex particles, proved a rapid, simple method for detecting circulating antibodies to L pneumophila in a one minute slide latex agglutination test. There was good correlation with the indirect immunofluorescence antibody test (IFAT), and the specificity and sensitivity with respect to a diagnostic result were 98.3% and 97.6%, respectively, using a series of well characterised sera. The latex agglutination test seems well suited as a screening test for presumptive cases of Legionnaires' disease; the latex reagent is easy to prepare and seems to remain stable at 4 degrees C for up to six months.